Ramadan Tradition and Social Piety Reproduction in Indonesia - Shalihin, Nurus; Azwar, Welhendri; Yusuf, M; Hulwati, Hulwati (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This article aims to illustrate the power of Ramadan as a social space where the Muslim community can reproduce piety. Data were obtained through interviews, documentation, and surveys. The findings of this study highlight two important aspects that characteristically mark Ramadan as a social space. First, Ramadan has become a social arena for Muslims where piety and generosity suddenly emerge as identities continually contested by Muslims. Second, the sudden social patterns of piety and generosity observed among Muslims during Ramadan are shaped by the intersection of religion and local traditions such as padusan and balimau, nyadran and ziarah kubro, along with perlon unggahan and magengan. Therefore, with these findings, we assert that Ramadan not only functions as a social arena but also becomes a third space where society blends religion and tradition, simultaneously strengthening their identity and social status throughout the month of Ramadan